Constraints Faced by the Inorganic Farmers in the Eastern Plain of Rajasthan (International Journal of Food and Nutritional Sciences, 2022)
This study was conducted in the eastern plain of Rajasthan. Conventional farmers are still facing various constraints; hence the study entitled “Constraints Faced by the Inorganic farmers in the Eastern Plain of Rajasthan” was conducted in eleven villages